2022
DOI: 10.1155/2022/9139766
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Coffee Husk Fuel Briquettes as an Alternative Energy Source

Abstract: Biomass energy accounts for more than 92 percent of overall energy consumption in Ethiopia. As a result, Ethiopia is one of the world’s most biomass-dependent countries. The high reliance on wood fuels and agricultural residues for fuel harms society’s social, economic, and environmental well-being. This study aims to create and test the quality of fuel briquettes made from the coffee husk. Also built and produced are a carboniser/charcoal kiln, a manually operated molder system, and a briquette stove for burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
0
15
1
1
Order By: Relevance
“…This is corresponding to the rapid growth of population, urbanization, and industrialization [ 3 ]. It is detrimental to society's social, economic, and environmental well-being that so many people still rely heavily on conventional energy sources for lighting, heating and cooking [ 9 ]. Most households in the country frequently use three-stone fires for cooking as their primary energy source, which causes indoor air pollution and detrimental health effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is corresponding to the rapid growth of population, urbanization, and industrialization [ 3 ]. It is detrimental to society's social, economic, and environmental well-being that so many people still rely heavily on conventional energy sources for lighting, heating and cooking [ 9 ]. Most households in the country frequently use three-stone fires for cooking as their primary energy source, which causes indoor air pollution and detrimental health effects.…”
Section: Introductionmentioning
confidence: 99%
“…Indoor air pollution is brought on by the harmful smoke that solid biomass fuels emit when they are burned. Additionally, it has a detrimental effect on agricultural households' capacity for production while arousing worries about significant CO 2 emissions, local deforestation, and land degradation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using an open fire to cook releases harmful particles [11] that course several health problems and also deteriorate the rural household economy as well as the local and global environment. As a result of renewed interest in alternative energy sources, climate change and indoor air pollution are attempting to raise public concern about gasification [12] . One of the most significant renewable energy sources is biomass, and gasification offers a viable method for producing clean, low-emission synthetic fuels [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Lubwama et al [23] demonstrated that rice and coffee husks briquettes had superior thermal efficiency compared to groundnut shells. Briquettes from coffee husks were also studied by Setter et al [24], revealing the effect of particle size on the mechanical and energy parameters of briquettes and by Tesfaye et al [25], presenting the benefits of coffee husk briquettes compared to firewood.…”
Section: Introductionmentioning
confidence: 99%